Porous anode of lithium–oxygen battery based on double-gas-path structure. (14th December 2017) - Cai, Kedi; Xiao, Yao; Lang, Xiaoshi; Tong, Yujin; He, Tieshi; Mao, Zhiming; Wang, Cheng
Abstract: A lithium–oxygen battery of double-gas-path structure and porous anode is presented in this work. Different from traditional structure battery, porous anode and the gas channel of anode side are used to provide argon gas for the battery. In order to protect the anode from corrosion of oxygen which penetrates from the cathode to the anode by dynamic gas-phase equilibrium. The improvement of the battery performance is attributed to the novel structure that can protect lithium metal from the corrosion of oxygen and it also reduces the growth of dendrite. The lithium–oxygen battery based on double-gas-path structure shows long cycle life (38 cycles), high discharge specific capacity (2510 mAh g −1 ) and specific energy density (7200 W h kg −1 ). More importantly, this work will also provide new ideas and methods for the research of other metal-air battery. Highlights: Put forward a new kind of lithium-oxygen battery with double-gas-path structure and porous anode. The novel battery structure can reduce the corrosion of lithium metal and the growth of dendrite. Compared with the traditional structure battery, the new battery has a good cycle performance.